Analysis of substrate selectivity determinants in Ubiquitin Specific Proteases 11 and 15 - Mayer, Matthias (2023)
Ubiquitin Specific Proteases (USPs) have long been studied for various physiological effects, being involved in many cellular processes as well as many different cancers. The variety of the USP family as well as the large variation in substrates has made them the subject of drug trials in the past. However, as one USP can target many different substrate in cells, more work should be done to analyse what directs this substrate specificity. This investigation aims to elucidate which amino acids direct the substrate specificity of USPs. USP11, a poor cleaver of linear diubiquitin, was analysed using sequence analysis and a previous structure to identify amino acids which affect substrate specific activity. This aspartic acid residue proximal to the catalytic histidine (USP11D886) was shown to affect cleavage of linear diubiquitin, with a glycine in this position drastically increasing cleavage rates. The reverse mutation in USP15 (USP15G860D) demonstrated complementary results. However, two binding forms leads to a complex analysis of the interaction through isothermal titration calorimetry (ITC) and microscale thermophoresis (MST). An X-ray crystallography derived structure with novel protein tags to aid crystallographic study shows evidence of multiple binding sites between USP11 and diubiquitin. This showcases a promising target for substrate specific activity, with the proximal aspartic acid/glycine residue being a druggable target for specific interactions.